Brexit as a (de)politicized issue? Evidence from Czech and Slovak parliaments. Issue 4 (2nd October 2021) - Kaniok, Petr; Brusenbauch Meislova, Monika
ABSTRACT: The article engages in the debate about the extent of the domestic politicization of Brexit in the EU27, and the causes and agents thereof. More specifically, it examines which parliamentary actors in Czechia and Slovakia have tried to de/politicize Brexit, and which strategies they have applied while doing so. By inquiring into the concrete de/politicization moves by different agents within parliamentary arenas, we attempt to open up the black box of the de/politicization processes associated with Brexit. Empirically, the article relies on original data from a large-scale quantitative content analysis of parliamentary deliberations on Brexit between 2016 and 2019. We argue that Brexit is largely depoliticized in Czech and Slovak Parliaments, with many factors intimately interlinked and jointly at work in its de/politicization. At the same time, we show that the lines of conflict on Brexit run in multiple directions and that the government/opposition status, left/right scale placement and the pro-EU/anti-EU approach appear to be important factors of parliamentarians' tendencies to de/politicize the Brexit issue. As such, our findings help explain a key puzzle in the withdrawal process, namely why Brexit and its repercussions have not matured into a political issue that is being politicized within EU27 domestic politics.